A novel role of lamins from genetic disease to cancer biomarkers - Kunnathur Murugesan Sakthivel; Poonam Sehgal (Frontiers Media S.A., 2016)
Lamins are the key components of the nuclear lamina and by virtue of their interactions with chromatin and binding partners act as regulators of cell proliferation and differentiation. Of late, the diverse roles of lamins in cellular processes have made them the topic of intense debate for their role in cancer progression. The observations about aberrant localization or misexpression of the nuclear lamins in cancerous tissues have often led to the speculative role of lamins as a cancer risk biomarker. Here we discuss the involvement of lamins in several cancer subtypes and their potential role in predicting the tumor progression.